Physical variables - lake temperature profile from Almbergasjön, limnic profile - Abisko Scientific Research Station (Swedish Polar Research Secretariat, 2023)
High frequency temperature profiles are measured in lakes of SITES Water to be able to determine the thermal structure.
Abisko Scientific Research Station (2023). Physical variables - lake temperature profile from Almbergasjön, limnic profile, 2017-06-21–2017-10-05 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/3cL602gJRb70-jqpquho8uKH
Keywords: Abisko Scientific Research Station; Time instant; Time instant; Water temperature; Water temperature; Sediment temperature; Sediment temperature; Water depth; Water depth; Standard deviation reading of TW within output interval; Standard deviation reading of TW within output interval; Standard Deviation of TSED; Standard Deviation of TSED; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap